L’avion, facteur d’uniﬁcation du Bassin caraïbe ? - Colette Ranély Vergé‑Dépré; Patrice Roth (M@ppemonde)
Air transport activity has long played an exceptional role in the Caribbean Basin. In this extroverted space, this activity represents major economic and political stakes. While Caribbean countries are trying to strengthen regional solidarity, does the air transport industry encourage this space to open up to the outside world or, on the contrary, does it ensure a greater territorial cohesion?